Gabon : Statistical Annex. (IMF Staff Country Reports; Country Report ;, 2004)
Income and social indicators, GDP by current prices, supply and use of resources at current prices, savings and investment balances, crude oil production and prices, capital expenditure and oil exploration, discovered oil fields, mineral production, exports, and prices, production and export of timber, production of agriculture, livestock, and fishing, industrial production, wood production and prices, production and distribution of electricity and water, transportation, monetary indicators, interest rate structure, foreign trade indicators, international reserves, composition of exports and imports, and balance of payments are listed in this study.